Bioinformatics analysis and spatiotemporal distribution of the f lic gene and its protein isolated from Escherichia coli-infected patients in Eastern Algeria - Harrar, Abdenassar; Awang Hamat, Rukman; Hamidechi, Mohamed Abdelhafid (Penerbit Universiti Sains Malaysia, 2024)
Background: The fliC locus in Escherichia coli primarily encodes flagellar (H) antigens. Exploring fliC sequence diversity will shed light on the mechanisms of bacterial pathogenicity. This study examined the presence of fliC mutant strains of E. coli in infected patients from different age groups, sexes and sample types in eastern Algerian provinces over a span of 2 years. Methods: This retrospective, cross-sectional study involved three provinces in eastern Algeria: i) Bordj Bou Arreridj, ii) Setif and iii) Batna. A total of 75 E. coli isolates were obtained from the University State Hospital Centre. Two types of analyses were conducted: i) a bioinformatics analysis of the protein sequences translated from the fliC genes, specifically the fliC f lagellar sequences and ii) a multifactorial statistical analysis (multiple correspondence analysis [MCA]) of the population of infected patients, considering various parameters. The fliC protein sequences were aligned using the Multiple Alignment using Fast Fourier Transform (MAFFT) programme. The alignment results were then visualised using the MView programme. Finally, a phylogenetic tree was constructed using the maximum likelihood algorithm in MEGA 11 software. Results: Bioinformatics analysis highlighted the strong conservation of the structures of the fliC protein sequences, especially at the two N- and C-terminal ends, and strong variability in the central zone. This remarkable fliC intersequence similarity is corroborated by the presence of protein motifs identified in the PROSITE protein motif database. Conclusion: fliC mutations in E. coli were not detected in the clinical samples of patients from hospitals in the three Algerian Provinces. Our analysis revealed that all the samples exhibited characteristics of wild-type virulent bacteria without mutations. A multicentre study is warranted for epidemiological surveillance of fliC mutant strains for future preventive measures.